Comparison Between MRAS and SMO Based Sensorless Control Methods of Permanent Magnet Synchronous Motor - Aydın, Çağlar; Unal, Sencer; Özdemir, Mehmet (My University, 2021)
This paper presents a comparison between sliding mode observer and model reference adaptive system based sensorless position and speed control of permanent magnet synchronous motor. In traditional sliding mode observers, signum function, which is used as switching function, causes chattering effect. To reduce chattering effect, low pass filter is used but this filter introduces a phase delay. In order to eliminate these problems, a sigmoid function is used instead of signum function in sliding mode observer based control method. In model reference adaptive system based control method, it is purposed to make error zero between the reference model and adjustable model. Popov’s super stability theorem is used for the stability of model reference adaptive system control method. Both of the control methods are simulated with Matlab/Simulink.
Keywords: Pmsm; Mras; Smo; Sensorless